2021
DOI: 10.1111/1365-2745.13619
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of weed dispersal by wintering gulls within and beyond an agricultural landscape

Abstract: 1. Non-frugivorous waterbirds disperse a wide variety of plants by endozoochory, providing longer-dispersal distances than other mechanisms. Many waterbirds visit both agricultural and natural landscapes during their daily movements, but potential bird-mediated dispersal of weed plants within and from agricultural landscapes to other habitats is commonly overlooked. Gulls (Laridae) are expanding in numbers and increasingly exploiting anthropogenic habitats worldwide, with possible growing implications for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 79 publications
(123 reference statements)
1
42
3
Order By: Relevance
“…Silva G. G. et al, 2021) showing that differences in the species composition of seeds dispersed by waterfowl species are related to their foraging behavior (note, these studies did not consider plant traits). In contrast, a study of other waterbirds in rice fields found no difference between a gull and stork species in the plants they dispersed (Martín-Vélez et al, 2021). Ours is the first study showing that both bird and plant traits drive waterfowl-seed interactions.…”
Section: Different Waterfowl Have Different Roles As Seed Vectorscontrasting
confidence: 58%
See 1 more Smart Citation
“…Silva G. G. et al, 2021) showing that differences in the species composition of seeds dispersed by waterfowl species are related to their foraging behavior (note, these studies did not consider plant traits). In contrast, a study of other waterbirds in rice fields found no difference between a gull and stork species in the plants they dispersed (Martín-Vélez et al, 2021). Ours is the first study showing that both bird and plant traits drive waterfowl-seed interactions.…”
Section: Different Waterfowl Have Different Roles As Seed Vectorscontrasting
confidence: 58%
“…These birds mainly disperse seeds via gut passage (endozoochory), yet their importance for plants lacking a fleshy-fruit has been underestimated because it is ignored by widely used "dispersal syndromes" (Green et al, 2021). Many of the migratory bird species are waterbirds, which are important for the dispersal of a broad range of both aquatic and terrestrial plants between habitat patches, often facilitating dispersal at extreme distances of >100 km (Green et al, 2016(Green et al, , 2021Viana et al, 2016;Martín-Vélez et al, 2021). The waterbird group best known for seed dispersal is that of the waterfowl (Anatidae: ducks, swans and geese) (Green et al, 2016(Green et al, , 2021Soons et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst 576 species considered not to be dispersed by birds, they include 174 from genera identified as duck‐dispersed by Soons et al 2016 (including 58 taxa in common at the species level). For example, Tamme et al (2014) suggested that Juncus bufonius had an MDD (via wind) of only 100 m, yet this species is dispersed by numerous ungulates and waterbirds, including gulls providing an estimated MDD of > 200 km (Albert et al 2015a, Lovas‐Kiss et al 2019, Martín‐Vélez et al 2021b). As further examples of how databases can mislead, none of 247 Poaceae and 165 Cyperaceae species in an Australian database were considered as dispersed via endozoochory (Thomson et al 2010), yet avian endozoochory is particularly frequent in these families (Calviño‐Cancela et al 2006, Green et al 2008).…”
Section: When They Ignore Key Vectors Plant Trait Databases Are Unreliablementioning
confidence: 99%
“…Pellets contain undigested food items, and are normally produced at roosting sites at the end of the day. Shorter maximum gut retention times and dispersal distances are expected for propagules egested in pellets than for faeces (Martín-Vélez et al 2021b). Like seeds, small invertebrate propagules stuck on the outside of crayfish are liable to be ingested and dispersed by these birds (Lovas-Kiss et al 2018).…”
Section: Aquatic Sciencesmentioning
confidence: 99%
“…This study was carried out across seven sites in Andalusia used for roosting and feeding by L. fuscus, including ricefields (where C. ciconia were also sampled), landfills, salt pans, and a natural lake (Table 1; Fig. 1), with a known and varying extent of connectivity through direct L. fuscus flights (Martín-Vélez et al 2020, 2021b. These sites are described as follows (see Martín-Vélez et al (2020, 2021c for more details):…”
Section: Study Sitesmentioning
confidence: 99%